Mandibular Angle Fracture Treated With New Three-Dimensional Grid Miniplate - de Melo, Willian Morais; Antunes, Antonio Azoubel; Sonoda, Celso Koogi; Hochuli-Vieira, Eduardo [UNESP]; Cabrini Gabrielli, Marisa Aparecida [UNESP]; Real Gabrielli, Mario Francisco [UNESP] (Lippincott Williams & Wilkins, 2012)
Fractures of the mandibular angle deserve particular attention because they represent the highest percentage of mandibular fractures and have the highest postsurgical complication rate, making them the most challenging and unpredictable mandibular fractures to treat. Despite the evolution in the treatment of maxillofacial trauma and fixation methods, no single treatment modality has been revealed to be ideal for mandibular angle fractures. Several methods of internal fixation have been studied with great variation in complications rates, especially postoperative infections. Recently, new studies have shown reduction of postsurgical complications rates using three-dimensional plates to treat mandibular angle fractures. Nevertheless, only few surgeons have used this type of plate for the treatment of mandibular angle fractures. The aim of this clinical report was to describe a case of a patient with a mandibular angle fracture treated by an intraoral approach and a three-dimensional rectangular grid miniplate with 4 holes, which was stabilized with monocortical screws. The authors show a follow-up of 8 months, without infection and with occlusal stability.
Keywords: Bone plates; fracture fixation; internal fixation; mandibular angle fracture; osteosynthesis